Keterampilan Merias Wajah Melalui Metode Tutor Sebaya Bagi Anak Tunarungu - Gustina Gustina; Marlina Marlina (Universitas Negeri Padang, 2021)
This research was motivated by two students who lacked motivation of students to develop student skills, where the teacher had not used good teaching methods in teaching skills to use tools and materials in make-up. This research is a classroom action research conducted collaboratively. This research was conducted in two cycles, each cycle consisting of three meetings (including one meeting for the final test). The subjects of this teacher's research were 2 grade students of class VIII. The research instruments used in this study were student activity observation sheets, student practice tests and tutor observation sheets and teacher activities. The results showed the application of the peer tutor method to makeup skills, namely (a) the planning stage was carried out by the researcher by preparing lesson plans and instruments. (b) the implementation stage is carried out by teachers and tutors. (c) the observation stage carried out by the researcher and the observed observer is two aspects, namely the process and the results of learning skills. During the learning process, there was an increase in the quality of make-up skills shown by student activities where there was an increase in student activity from cycle I to cycle II. In the student practice test there was an increase from cycle I to cycle II. Then in teacher activity there was also an increase from cycle I to cycle II. (d) Reflection on the first cycle of the application of the peer tutor method can improve learning outcomes for makeup skills. Thus it can be concluded that the application of the Peer Tutor method can improve the results of makeup skills in class VIII SLB Kemala Bhayangkari Lintau Buo Utara, Tanah Datar.